K-12 online education during COVID-19 pandemic: Private school teachers' perspective - Eric M. Ragpala (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Throughout the COVID-19 pandemic, most educational institutions had been compelled to make an abrupt transition to online classes, which provided opportunities and challenges for students and teachers. To make sure the validity and reliability of this research study, a descriptive design was used. The researcher utilized an online semi-structured interview to gather the needed data from the participants. The researcher adhered to random sampling in selecting the participants of the study. A total of 17 private school teachers were randomly interviewed using Google Meet and Zoom. After the online semi-structured interview, the researcher analyzed the data using thematic analysis. The three major themes generated from the responses of the participants are perceptions of the private school teachers, the challenges in online teaching amidst the COVID-19 pandemic, and coping mechanisms. The study found that online teaching had an impact on the responsibilities and roles of the participants in K-12 education due to the changes in teaching platforms, procedures, and techniques. The study presented that the internet connection of students and teachers is one of the most important tools in online teaching. This study revealed also that pure online teaching will not help K-12 education achieve its goals due to the lack of hands-on activities. The study highlighted that the various challenges in online teaching encourage them to be adaptable and resourceful in their teaching careers. Furthermore, the study consists of coping mechanisms that determine how the participants coped with the changes introduced by the rapid move from face-to-face delivery of lessons to online teaching. The researcher recommends that teachers must regularly attend training and seminars on educational development and students must interact with their teachers to perform effectively in the teaching-learning process.